Survival strategy in the disruption era: The mediation of knowledge sharing in the effect of digital leadership on service innovation in the Indonesian hotel industry - Dicky Hida Syahchari; Arif Zulkanain; Azizah Omar (Jurnal Manajemen dan Pemasaran Jasa, 2026)
The research aims to investigate whether digital leadership has a direct impact on service innovation in organisations, with knowledge sharing serving as an intervening mechanism to examine how this correspondence functions. A quantitative method and a cross-sectional design were used in the study, which collected data through questionnaires from 258 employees working in 3- and 4-star hotels in Jakarta, Indonesia. Partial Least Squares Structural Equation Modelling (PLS-SEM) was used to test the hypothesised relationships. The results demonstrate that digital leadership has a positive, significant effect on service innovation. In addition, the findings reveal that knowledge sharing acts as a strong mediating factor, indicating that one of the most essential ways digital leaders foster innovation is by promoting a knowledge-sharing process that encourages employees to share information and knowledge freely in a collaborative environment. It underscores that leadership Influence operates, in part, through the development of organisational members’ capacity to learn. The study finds that digital leadership drives competitive advantage in the service sector and that its power is contingent on knowledge sharing. It underscores the strategic challenge for hotel managers to cultivate digital leadership competencies and progressively engineer organisational norms and infrastructures that promote and enable knowledge-sharing behaviours among employees, thereby facilitating sustained service innovation.